Masticatory efficiency, bite force and electrical activity of the masseter and temporalis muscles in bodybuilders - Júnior, Murilo-César-Bento-Laurindo [UNESP]; Goiato, Marcelo-Coelho [UNESP]; de Caxias, Fernanda-Pereira [UNESP]; Turcio, Karina-Helga-Leal [UNESP]; da Silva, Emily-Vivianne-Freitas [UNESP]; Deusdete, Michel-da Silva; dos Santos, Daniela-Micheline [UNESP] (Medicina Oral, S.L., 2021)
Background: This study aimed to compare the masticatory efficiency, the maximum voluntary occlusal bite force (MVOBF) and the electrical activity (EMG) of masticatory muscles of practitioners of upper limb bodybuilding before and after physical activity. Methods: Twenty healthy individuals (10 men and 10 women, age from 18 to 30 (mean of 24.7 years old) without masticatory system disorders, that regularly practice hypertrophic physical activity were submitted to the analyses of masticatory efficiency, MVOBF, and surface EMG of the temporalis and masseter muscles. The masticatory efficiency was analyzed by comminution of the artificial material (Optocal®) and a sieving method. The MVOBF was measured by a dynamometer, and EMG was evaluated during resting mandibular position, maximum voluntary clenching (MVC), and MVC with a Parafilm M tape between teeth, and free mastication of chewing gum. The analyses were made before (T0) and immediately after the performance of upper limb bodybuilding exercises (T1). The data of masticatory efficiency and MVOBF were submitted to the Student T-test, and their correlations were analyzed by the Pearson correlation test, and the EMG data were submitted to the 2-way repeated measures ANOVA, all tests with a 5% significance. Results: There was a significant decrease of masticatory efficiency after the training. No statistical difference in the MVOBF and EMG was found, and there was a positive correlation between masticatory efficiency and MVOBF. Conclusions: Therefore, changes were found for masticatory efficiency only, which decreased after hypertrophic exercise. There was a positive correlation between masticatory efficiency and MVOBF
Keywords: bite force; electromyography; Masticatory efficiency; physical activity